FINANCING PUBLIC UNIVERSITIES WITH RESOURCES GENERATED BY BUSINESS ENTERPRISES - Javier Melgarejo, Leoncio (2012)
The state has commissioned its universities a particular academic mission: to research, to form, and to extend. These are established both by the Constitution and the Organic Law of Universities No. 23733, which also points out: “the national community sustains economically the universities, and this will correspond with quality of services …. and it is the responsibility of the state to provide an adequate amount of resources to maintain and promote the standards achieved by Higher Education.“ However, the Treasury allocates only an average of 50% of its budget, thus making it difficult to reach its mission and generate its own resources via production centers and the like. In these times of competition without barriers, it is urgent that these companies generate goods and services benefiting from the scope of mercantile laws to achieve sufficient profits, and thereby enabling universities to finance its budget targets as established in the Four Final disposition of the law on the National Public Budget.